Study on the Conductivity Effect on the Characteristics of a Wideband Printed Dipole Antenna Implemented with Silver Nanoparticle Ink - Wang, Heesu; Kwon, Ohjin; Park, Yong Bae; Han, Haewook; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2024)
This study examined a flexible composite wideband dipole antenna implemented with conductive silver nanoparticle ink having different conductivities. Two identical split ring resonators (SRRs) were designed to encompass each arm of a dipole element, and each dipole arm and its coupled SRR were printed on the top and bottom sides of a dielectric substrate. The overall dimensions of the compact antenna were 10 mm × 74.8 mm × 0.254 mm (0.053λo × 0.399λo × 0.0014λo at 1.6 GHz). The characteristics of the antenna with different conductivities were numerically investigated and experimentally confirmed. Our investigation aimed to ascertain the proposed antenna’s response to different conductivity values and to determine the range of conductivity values that generates major changes in the antenna’s performance characteristics in terms of impedance bandwidth, gain, and radiation efficiency. At conductivity values less than approximately 6.0 × 104 S/m, the number of generated resonances changed from three to two, and the antenna experienced a nearly 3-dB gain reduction when the conductivity approached 5.8 × 104 S/m.
Keywords: Composite Antenna; Conductive Materials; Flexible Antenna; Silver Nanoparticle; Split Ring Resonator (SRR); Wideband Dipole Antenna